Serum Syndecan-1 levels in patients with immunoglobulin A vasculitis in children - Xinyi Jia; Zhenya Zhu; Jing Miao; Linqian Zhang; Xiaobing Li; Yunguang Bao; Mizu Jiang (Jornal de Pediatria, 2022)
Objective: The aim of this study was to evaluate the serum Syndecan-1 (SDC-1) levels in patients with immunoglobulin-A vasculitis (IgAV) in children and its relation with gastrointestinal involvements. Methods: Sixty-eight children with IgAV and 48 healthy children were enrolled in this cross-sectional study. Clinical and related laboratory data were collected from a computerized hospital database. Serum SDC-1 was collected on admission prior to treatment. Results: Forty-eight patients fully met the IgAV diagnostic criteria at admission (IgAV group), 20 patients with rash only and diagnosed IgAV during hospitalization (Purpura group). In IgAV group, 30 patients with gastrointestinal involvements (IgAV-GI group) and 18 patients without gastrointestinal involvements (IgAV-NGI group). SDC-1 serum levels were significantly higher in the IgAV group (86.37 ng/mL (IQR 59.16–117.14 ng/mL)) than in the controls (20.37 ng/mL (IQR 15.52–26.45 ng/mL)) and the Purpura group (32.66 ng/mL (IQR 14.87–49.89 ng/mL)). Additionally, SDC-1 (OR = 1.08) was independently associated with IgAV with a cut-off value (sensitivity and specificity) of 66.55 ng/mL (68.8%, 95.0%), and the area under the curve was 0.908. The serum SDC-1 levels of the IgAV-GI group (106.92 ± 50.12 ng/mL) were significantly higher than those in the IgAV-NGI group (67.52 ± 17.59 ng/mL). Logistic regression analysis showed that SDC-1 (OR = 1.03) was independently associated with IgAV-GI with a cut-off value of 89.39 ng/mL. Conclusions: SDC-1 serum levels may mirror vascular endothelium injury and mucosal damage in IgAV. Its applicability as a surrogate biomarker in IgAV remains to be determined.